Effect of Personalisation of Instruction on Students' Anxiety in Mathematical Word Problems in Nigeria - A.O.A. Awofala (University of Sofia, 2017)
This study determined the effect of personalisation of instruction on the anxie-ty in mathematics word problems of 450 senior secondary school year two stu-dents in Nigeria within the blueprint of quasi-experimental research of Solo-mon four non-equivalent control group design. It also examined the influence of ability level on anxiety in mathematics word problems and personalisation was accomplished by incorporating selected information with students' per-sonal preferences into their mathematics word problems. Anxiety in mathemat-ics word problems was measured by the mathematics word problems anxiety questionnaire and data collected for the study were analysed using the inde-pendent samples t-test, paired samples t-test and one-way ANOVA. The re-sults showed significant main effect of personalization of instruction on stu-dents' anxiety in mathematics word problems whereas no significant main ef-fect of ability level was found on the dependent measure. Personalisation of instruction was found to have reduced students' anxiety in mathematical word problems.